Endobronchial brachytherapy as definitive treatment for endobronchial metastasis after surgery of non-small cell lung cancer - Atsushi Ito (BMC, 2021)
Abstract Background Endobronchial metastasis is a very rare type of recurrence after lung cancer surgery. Surgical intervention may be difficult to perform due to the postoperative reduction in the activities of daily living (ADL) and the invasiveness associated with redo surgery. In such cases, endobronchial brachytherapy (EBBT) plays an important role not only as a palliative treatment, but also as a definitive treatment with curative intent. Case presentation Three men (64, 69, and 74 years old) underwent combination therapy of external beam radiation therapy (EBRT) and EBBT for endobronchial metastasis after lobectomy of stage I–II non-small cell lung cancer (NSCLC): 2 cases of squamous cell carcinoma and 1 of adenocarcinoma. We used a special source-centralizing applicator for EBBT to avoid eccentric distribution of the radiation dose. Follow-up was considered to start from the end of brachytherapy. None of our patients experienced severe adverse events, and none needed extensive outpatient treatment. Local control was achieved in all cases by a bronchoscopic evaluation. All patients were alive after 31, 38, and 92 months of follow-up, respectively. In the adenocarcinoma patient, two metastases to the lung were discovered 3 years after EBBT, and the patient underwent partial wedge resection. Conclusions EBBT may be a promising treatment with curative intent for endobronchial metastasis after surgery of NSCLC.